Globalization, Financial Development and Regional Economic Dynamics: asymmetric panel evidence from Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2011)
This paper examines how regionalization in the face of globalization has affected financial development in the context of banking system efficiency in Africa. Results which are robust to financial system efficiency and growth-led-finance nexus reveal that in the post-regionalization era: (1) UEMOA and CEMAC regional banks' ability to finance credit by deposits has reduced; (2) financial institutions of COMESA have improved their capacity to fund openness related activities/projects with deposits; (3) increase in welfare has positively affected the intermediary role of banks; (4) globalization tends to be more detrimental to financial systems of 'economic and monetary' regions than to those of purely economic regions. As a policy implication, national and regional authorities should gain knowledge of the fact that with openness, the role of domestic and regional banks seems to lessen in the funding of openness related activities and projects. Much needs to be done on the improvement of infrastructure that curtails information asymmetry in the banking industry.
Keywords: A10; D60; E40; O10; P50; 330; Globalization; Financial Development; Regional Integration; Panel; Africa